Pathogen removal from municipal wastewater in Constructed Soil Filter - Kadam, Avinash M.; Oza, Goldie H.; Nemade, Pravin D.; Shankar, Hariharan S. (Ecological engineering, 2008)
In this work, a Constructed Soil Filter (CSF) system has been configured for the treatment of wastewater wherein we recreate a soil ecosystem for water purification. Purification capacity and seasonal variability of three such CSF facilities for indicator organisms as well as enteric pathogens monitored over 9–17 months are presented. Indicator organisms include total coliform, fecal coliform, fecal streptococci, heterotrophic plate count, Enterococcus fecalis, actinomycetes, and coliphage. Enteric pathogens include Escherichia coli 25922, E. coli O157:H7, Klebsiella pneumoniae, Pseudomonas aeruginosa, Clostridium perfringens, Staphylococcus aureus, Proteus mirabilis. All three sites show bacterial removal rate constant ( k d) in the range of 0.4–1.3 h −1 which is very high in comparison to the reported values from field as well as lab studies. Log removal for pathogens is typically 2–3 log orders. However, by extended recycling up to 5 log orders removal could be achieved. Among the three sites, k d values were in the order of site II > site I > site III, which is also the order of their commissioning, suggesting that these system matures with age. Low hydraulic retention time (0.5–2.0 h), no pretreatment, high removal efficiency, no mechanical aeration, very low energy requirement, and green ambience are the unique features of CSF.